ЕФЕКТИВНІСТЬ ПЕРЕДПОСІВНОЇ ІНОКУЛЯЦІЇ У ВИРОЩУВАННІ СІЛЬСЬКОГОСПОДАРСЬКИХ КУЛЬТУР ЗА РІЗНИХ ОРГАНІЧНИХ АГРОФОНІВ - Сидоренко, В. П.; Волкогон, В. В.; Дімова, С. Б.; Волкогон, К. І.; Луценко, Н. В.; Штанько, Н. П.; Земська, І. А. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2021)
Objective. Study the competitiveness, complementarity and symbiotic activity of a new strain of chickpea nodule bacteria Mesorhizobium ciceri ND-64, study the influence of seed inoculation on the productivity and yield of chickpea varieties of Ukrainian selection under their cultivation in different soil and climatic zones of Ukraine. Methods. Serological, gas chromatography, field experiment and statistical. Results. The use of a new strain of M. ciceri ND-64 for pre-sowing bacterization of chickpea seeds of varieties Skarb, Admiral, Odysei, Budzhak, Triumf and Pamiat upon growing in field experiments in the Steppe zone against the background of the local population of nodule bacteria contributes to a significant increase in nitrogen-fixing nodules by 5 % to 67 %, an increase in the mass of nodules by 10 % to 67 % and nitrogenase activity 26 % to 150 % compared with the positive control (inoculation with the reference strain of M. ciceri H-12). The use of M. ciceri ND- 64 for pre-sowing bacterization of chickpea seeds under cultivation in the Steppe zone of Ukraine also had a positive effect on increasing the yield of chickpea — by 4 % to 18 % compared to the positive control. Inoculation with a new strain of chickpea seeds of varieties Skarb, Triumf and Pamiat contributed to the formation of higher number of nodules (by 57 % to 89 %), increaseed mass of nodules (2.2–2.9 times) and their nitrogenase activity (2–4 times) compared with the positive control upon cultivation in the Polissia zone on the fields where there is no population of chickpea rhizobia. Under these conditions, an increase in structural parameters of yield, the highest gain in chickpea yield, increase in photosynthetic activity and protein content in grain upon inoculation with M. ciceri ND-64 was shown. Obtaining a specific antisera by immunization of rabbits allowed to detect serological relatedness of M. ciceri ND-64, M. ciceri H-101, Mesorhizobium sp. ND-601 and M. ciceri ND-64, isolated from chickpea nodules of Skarb and Pamiat varieties. The competitiveness of M. ciceri ND-64 was determined using the immunological method in the field experiment. It was found that 100 % of nodules have been formed by the representatives of M. ciceri ND-64 in the variant where this serological group was applied for inoculation in the variant with inoculation of the strain M. ciceri ND-64 100 % of the nodules were formed by representatives of this serogroup. Conclusion. M. ciceri ND-64 strain is an effective microsymbiont of chickpea plants, due to its virulence, competitiveness, nitrogen-fixing properties. According to the results of field experiments, it was shown that the new strain, complementary to all studied varieties differing in seed size and shape, type of bush and average height, forms an effective symbiosis for growing chickpea plants both against the active local population of rhizobia and upon the absence of M. cicerі population in the soil. Symbiotic parameters upon seed treatment with suspension of M. ciceri ND-64 exceed these values in the variants with inoculation using the reference strain of M. ciceri H-12 and strains isolated from the nodules of each study variety. Therefore, M. ciceri ND-64 can be used as a bioagent of a microbial preparation for inoculation of chickpea of different varieties in order to form an effective bean-rhizobial symbiosis, increase the productivity of this culture and improve seed quality.